TADARRUJ (BERANSUR-ANSUR) DALAM PELAKSANAAN HUKUM ISLAM MASA KINI - Mohd Nor, Amir Husin (Jurnal Syariah, 2019)
This article aims to address the significance of the gradual process (tadarruj) in the fonnation of Islamic law especially, during the time of the Prophet. Beside that, it also explains how the gradual process can be applied in the implementation of Islamic law in modem world.